ANALISIS GAYA BELAJAR MAHASISWA TERHADAP MODEL DAN STRATEGI PEMBELAJARAN DOSEN - Usman Noer (Al-Ishlah: Jurnal Pendidikan Islam, 2016)
Recognizing that every student, especially students choose a different learning styles, it is important to identify their learning style so that educators can prepare learning model and implement a strategy of learning that can accommodate all types of learning styles of students in order to increase motivation and involvement in learning activities. Implementation of the various models of learning by educators including professors will make the learning process more meaningful, but various models pembelajran the extent possible to make the learning process it managed to create a fun learning environment and can achieve academic achievement expected, the model pembejaran it should be raw and dynamic to dikreasikan the student's learning style atmosphere.